Global versus local brands in South Africa: an empirical analysis of consumer perceptions - Coetzee, Zandereen (School of Management Studies, 2020)
Global brands are increasingly expanding their footprint to developing countries, due to the promising opportunities that these countries hold; and as such, consumers are faced with the decision between global and local brands. In South Africa too, there has been an influx of global brands, which has placed pressure on the local retail landscape. Therefore, the main objective of this study was to determine whether there is a difference in perception among millennial consumers in South Africa between a global and a local fashion retail brand. Millennials are considered to be individuals born between the early 1980s and late 1990s. To understand consumers’ decision making process between global and local brands, the signaling theory was applied. The signaling theory is typically used to describe behaviour when multiple parties have access to different information – in this case it relates to consumers having access to the different signals sent out by both global and local brands. In addition to the signaling theory, the brand-analysis model was employed to measure these perceptions relating to brand-specific associations (perceived quality and emotional value), general brand impression (brand awareness and brand image) and brand commitment (brand loyalty and purchase intention). Therefore, the objectives and hypotheses for this study were directly derived from each of the brand-analysis constructs mentioned above. It is understood that researchers have not used the signaling theory and brand analysis model together. This study also considers them independently, however the brand analysis constructs are used as signals between brands and consumers. Using the two retail brands, H&M (global) and Mr Price (local) as stimuli, the data were collected through an online questionnaire. A non-probability sampling technique was implemented, which achieved a total sample size of n=263. The target population consisted of millennial consumers in South Africa, due to the significant spending power of this cohort. The findings were three-fold. Firstly, the hypotheses tests indicated that there are differences in consumer perception relating to each of the brand-analysis constructs, with higher ratings towards the global brand for perceived quality, emotional value, brand image, brand loyalty, and purchase intention. Local brands, however, appear to enjoy higher levels of brand awareness. Secondly, in order to gain deeper insights into these perceptions, this study also compared the difference in perceptions among the demographic subgroups. In contrast to the overall preference for global brands, certain groups, such as those with lower income levels and lower levels of education, had higher ratings for the local brand in terms of perceived quality, emotional value, brand loyalty and purchase intention. Lastly, the strength of the relationships between constructs was measured; and this showed that, for both brands, positive relationships exist among all of the brand-analysis constructs – with varying strength levels. The academic contributions of this study are as follows: In general, brand management literature in developing countries has been neglected. Previous research has shown that there are differences in brand perception between consumers from developed and those from developing countries. This study therefore aimed to add to the literature, not only towards a typical developing country, but towards a hybrid country, namely South Africa. In addition, the brand-analysis model and the signaling theory used in this study, serve as a basis for future research aiming to evaluate consumer choice. Practical contributions include the following: The findings yielded significant insights into the aspects to be emphasised by global and local brands, in order to be successful in capturing and maintaining the desire of consumers to purchase and use their brands. Thus, the findings provide an understanding of the drivers of global and local brand purchases for marketing practitioners – to improve or adjust their marketing strategies. On the basis of these findings, local brands are advised to invest in expanding their presence in other countries, and to advertise this as a signal of quality. Another strategy for local brands is to emphasise their authenticity and pride in the local culture as a signal of a deep connectedness with the local market. Global brands on the other hand, are advised to advertise their worldwide availability and acceptance as a signal of quality and prestige, and to offer an opportunity for consumers to be part of the global-consumer culture.